Signaling under double-crossing preferences - Chia-hui Chen; Junichiro Ishida; Wing-chuen Suen (Osaka University, Institute of Social and Economic Research (ISER), 2020)
This paper provides a general analysis of signaling under doublecrossing preferences with a continuum of types. There are natural economic environments where indifference curves of two types cross twice, so that the celebrated single-crossing property fails to hold. Equilibrium exhibits a particular form of pooling: there is a threshold type below which types choose actions that are fully revealing and above which they choose actions that are clustered in possibly non-monotonic ways, with a gap separating these two sets of types. We also provide an algorithm to establish equilibrium existence by construction under mild conditions.
Keywords: D82; I21; 330; single-crossing property; double-crossing property; counter-signaling; pairwise pooling; mass pooling